2016
DOI: 10.1111/jvim.13964
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Development of Histiocytic Sarcoma in Bernese Mountain Dogs

Abstract: BackgroundHistiocytic sarcoma (HS) is a rare but aggressive malignancy in humans that is poorly responsive to existing treatments. Although rare in most breeds of dogs, HS is common in Bernese mountain dogs (BMDs).ObjectiveDetermine risk factors associated with development of HS in BMD.AnimalsA total of 216 BMD were registered with the Berner‐Garde Foundation.MethodsAn internet‐based cross‐sectional survey was used to collect information from owners of BMD diagnosed with HS and owners of disease‐free littermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Dogs in this study with PAHS were more likely to have had prior joint disease in their tumour‐affected joint when compared with the control population. The OR of 13.42 (95% CI: 4.33‐48.63, P < .0001) suggests there is a strong relationship between joint disease and development of PAHS; the existence of this association has been demonstrated previously in Bernese Mountain Dogs and this study confirms that the relationship exists in dogs of other breeds as well. Not all of the breeds reported in the current study have been previously suggested to be predisposed to HS.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Dogs in this study with PAHS were more likely to have had prior joint disease in their tumour‐affected joint when compared with the control population. The OR of 13.42 (95% CI: 4.33‐48.63, P < .0001) suggests there is a strong relationship between joint disease and development of PAHS; the existence of this association has been demonstrated previously in Bernese Mountain Dogs and this study confirms that the relationship exists in dogs of other breeds as well. Not all of the breeds reported in the current study have been previously suggested to be predisposed to HS.…”
Section: Discussionsupporting
confidence: 84%
“…Inflammation could therefore predispose to both cruciate rupture and PAHS. A recent report by Ruple et al demonstrated Bernese Mountain Dogs receiving prescription anti‐inflammatory medications had a lower risk of HS development, suggesting that inflammation may play a role in HS development in this breed . How the known genetic risk for HS in the Bernese Mountain Dog impacts the effect of inflammation in promoting HS development is not yet known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed HS predisposed breeds, especially BMD, are also predisposed to reactive histiocytic diseases 41 but also to other immune or inflammatory diseases such as glomerulonephritis, aseptic meningitis or inflammatory bowel disease (https://www.bmdca.org/health/diseases.php) 42,43 . While no causal relationship was proved between inflammation and HS, inflammation is suspected to contribute to HS development [44][45][46] . In these conditions it is not surprising that HS GWAS hits overlap not only candidate tumor suppressor genes (TUSC1) or well-known tumor suppressors involved in cell cycle (CDKN2A), in genome stability (telomere protection: POT1, replication stress/DNA damage: FHIT…) but also in inflammation (IL17a, IL17rd, SPNS3, ARHGEF3…) (Supplementary Table 7).…”
Section: Pleiotropic Effect Of Locimentioning
confidence: 98%